Early retirement incentive programs as a human resources restructuring strategy in public sector: Theoretical perspective - Manal Elsayed Shabat (Review of Economics and Political Science (REPS), 2020)
Purpose - The purpose of this paper is to analyze the conceptual framework about human resources downsizing and restructuring and how organizations of the public sector can do that effectively and efficiently. These facts drive to the conclusion that the implementation of early retirement incentives requires the most elaborate planning and execution to be effective, predictable and safe in the long term. Design/methodology/approach - This paper adopts an analytical, descriptive methodology approach to describe the basic features of the data by using the descriptive research design. Data have been collected through different sources, which include secondary data, to introduce the theoretical literature of the subject as books, journals, articles, published working papers and referred previous studies related to the same subject. Findings - Downsizing process is a deliberate administrative process that includes, but is not limited to, workforce reduction and is primarily aimed at achieving efficiency in public organizations. The definition of workforce downsizing may be narrowed to reducing the number of workers, or more likely to refer to general efforts to restructuring human resources in public organizations, Early Retirement Incentive Programs (ERIP) represents a viable alternative for organizations seeking to reduce staff. For the ERIP to be successful, the program coordinator must understand the business objectives and goals that the organization is trying to obtain. Originality/value - Human resources strategies concerning downsizing public administration workforce should be more appropriate to those who leave the organization and those who stay at work, reducing the negative psychological, administrative and economical effects. This could be achieved through a strategy called early retirement incentive programs.
Keywords: 330; Human Resources; Retirement; Downsizing; Restructuring; Older worker; Early Retirement Incentive Programs (ERIP)